Hospital Management Information System - Darwis, M; Soraya, Soraya; Nawangwulan, Kurniati; Ekawaty, Dian; Imran, Ali; Yusfik, Yusnita (International Journal of Health Sciences, 2023)
Information systems are an important factor for improving services as well as data savings for hospitals. Computerized service information systems are the right solution to solve problems. This research aims to determine the application of the Hospital Management Information System at Luwu District Hospital in improving service quality. The hospital management information system at Batara Guru Belopa Hospital includes three activities, namely input, process and output, which in its implementation is influenced by driving and inhibiting factors. The results of this research reveal that the RL 1, RL 2a, RL 2b reporting mechanisms created are incomplete and not in accordance with the Ministry of Health's regulations which should consist of RL 1, RL 2a, RL 2b, RL 3, RL 4, RL 5 and RL 6, So there are still obstacles in data processing, both manually and with computerized systems. The conclusion is that the resulting Management Information System does not support the reporting produced as feedback on the evaluation of the implementation of the programs being run.